Implementasi Model Prototype Pada Sistem Informasi Persediaan Bahan Baku Menggunakan Metode Economic Order Quantity - Elah Nurlelah; Fuad Nur Hasan; Reni Maryani (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Inventory is a variety of materials available from the business world to meet consumer demand every day, including materials such as raw materials and materials used in the production process. In inventory control, it is necessary to have a system for recording and calculating inventory, because inventory can affect the company's financial reports. CV Golden Toys is a company that operates in the manufacturing sector, in this company it is necessary to design an information system application for raw material inventory and use appropriate methods for raw material inventory in the hope of solving problems that arise such as large amounts of inventory piling up, data processing and search. Transactions or creating reports take a lot of time. By considering these constraints, the author created a web-based raw material inventory information system. In this research, the software model used is the Prototype model which is a method for building a system based on information needs quickly and efficiently. Meanwhile, the method used is the Economic Order Quantity (EOQ) method. This method is used with the aim of optimizing the total cost of raw material inventory and to find out the optimal number of orders for the system used. The results of this research are that a web-based raw material inventory information system and using a Prototype model and using the Economic Order Quantity method can help companies in terms of optimal procurement of raw materials, this can help reduce costs incurred by the company, besides that it can make things easier. warehouse in recording goods so that processing time becomes relatively faster